Study of BMI and Waist Hip Ratio of Indians with Type-2 Diabetes Mellitus - Purohit, Ashish; Tiwari, Varsha (International Journal of Medical Research and Review, 2014)
Introduction: Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. UCP2 locus on human chromosome 11 is linked to obesity and hyperinsulinism. Methods: A case control study was carried out in the Department of Medicine comprising 50 newly diagnosed type 2 diabetes mellitus patients and 50 healthy controls. All patients and controls were subjected to a detailed history physical examination and investigations. Information on age, sex, body weight, height, waist and hip circumference, and BMI (wt. (kg)/ht. (mtr2)) were obtained. Results: The body mass index (BMI) of the study subjects was cases - 23.94 ± 1.83 kg/m2, controls - 22.8 ± 1.38 kg/m2 (P < 0.001). Prevalence of an abnormal value of waist-to-hip ratio (WHR) was found to be 46% in the cases. Of the cases, 58% had poor glycemic control. Discussion and Conclusion: BMI is strongly and independently associated with the risk of being diagnosed with T2D. We found that, compared with normal BMI, overweight and obesity was statistically significantly associated with the risk of being diagnosed with T2D among individuals without any other prior evidence of T2D, suggests that the disease might be on track of changing its trend or the patients are reporting at a late stage due to health disparities. Central obesity was present in the studied population, with generalized obesity, making the population prone to insulin resistance. The mean values and the prevalence of abnormal values of BMI, WC, and WHR were higher in the cases than in the controls.